2018
DOI: 10.3747/co.25.4069
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as a Predictor of Advanced Colorectal Cancer Outcome and Cetuximab Treatment Response

Abstract: Background Adrenergic receptor stimulation is involved in the development of hypertension (htn) and has been implicated in cancer progression and dissemination of metastases in various tumours, including colon cancer. Adrenergic antagonists such as beta-blockers (bbs) demonstrate inhibition of invasion and migration in colon cancer cell lines and have been associated with decreased mortality in colorectal cancer (crc). We examined the association of baseline htn and bb use with overall (os) and progression-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…CRC is associated with a variety of factors. Representative factors include hypertension (42,43), folate (44,45), homocysteine (46), and diabetes milieus (47). Thus, treatment strategies and prognostic management methods change.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is associated with a variety of factors. Representative factors include hypertension (42,43), folate (44,45), homocysteine (46), and diabetes milieus (47). Thus, treatment strategies and prognostic management methods change.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were retrieved by filtering titles and abstracts, and 39 studies were excluded after full text review, and reasons why studies were excluded were listed in Supplementary Table S4 . Ultimately, we included 37 studies for our meta-analysis, including 20 publications concerning cancer risk ( Pahor et al, 1996 ; Michels et al, 1998 ; Rosenberg et al, 1998 ; Tenenbaum et al, 2001 ; Beiderbeck-Noll et al, 2003 ; Boudreau et al, 2008 ; van der Knaap et al, 2008 ; Friedman et al, 2011 ; Hallas et al, 2012 ; Jansen et al, 2012 ; Wang et al, 2012 ; Mansouri et al, 2013 ; Makar et al, 2014 ; Chang et al, 2015 ; Lin et al, 2015 ; Numbere et al, 2015 ; Grimaldi-Bensouda et al, 2016 ; Dierssen-Sotos et al, 2017 ; Cheung et al, 2020 ; Brasky et al, 2021 ), 17 regarding cancer prognosis ( Sorensen et al, 2000 ; Hicks et al, 2013 ; Holmes et al, 2013 ; Cardwell et al, 2014 ; Jansen et al, 2014 ; Giampieri et al, 2015 ; Osumi et al, 2015 ; Morris et al, 2016 ; Jansen et al, 2017 ; Weberpals et al, 2017 ; Sud et al, 2018 ; Bowles et al, 2019 ; Cui et al, 2019 ; Fiala et al, 2019 ; Mafiana et al, 2019 ; Ozawa et al, 2019 ; Ahl et al, 2020 ). Of these 37 studies, 26 studies used cohort design, three studies used nested case-control design, and 8 studies used case-control design.…”
Section: Resultsmentioning
confidence: 99%
“…However, such an effort is currently limited due to the lack of relevant experimental and clinical data about optimal blood pressure control strategy for tumor patients with hypertension. Epidemiological studies in recent years have shown that hypertension was significantly associated with an increased risk of kidney cancer, colon cancer, and postmenopausal breast cancer ( Han et al, 2017 ; Hidayat et al, 2017 ; Sud et al, 2018 ). Similarly, vascular endothelial growth factor signaling pathway inhibitors as common antineoplastic drugs are key contributors to raise blood pressure ( Agarwal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%